Evaluation of motor changes and toxicity of insecticides Fipronil and imidacloprid in Africanized Honey bees (Hymenoptera: Apidae) - Lunardi, J. S. [UNESP]; Zaluski, R. [UNESP]; Orsi, R. O. [UNESP] (Universidade Estadual de Feira de Santana, 2017)
Honey bees are important pollinators and are essential in beekeeping. Honey bees get exposed to systemic pesticides while foraging in contaminated fields, and it is important to know the toxicity (LD50) and evaluate the impacts of bees' exposure to these molecules. Fipronil and imidacloprid are systemic pesticides widely used in Brazil and other countries. The objective of this study was to determine the LD50 (24 hours) and evaluate motor changes in Africanized honey bee foragers exposed to lethal and sublethal doses of fipronil and imidacloprid. To determine the LD50, foraging honey bees were exposed by ingestion and contact to five doses of fipronil (Regent 800WG°) and imidacloprid (Appalus 200SC°) insecticides. After 24 hours of exposure, the number of dead bees was counted, and the results were subjected to probit analysis. The motor activity of bees exposed by ingestion or contact to LD50 and sublethal doses (1/500th of the LD50) of both pesticides was assessed 4 hours after exposure using a behavioral observation box. The ingestion and contact with LD50 of fipronil were 0.0528±0.0090 and 0.0054±0.0041 μg/bee, respectively; the ingestion and contact with LD50 of imidacloprid were 0.0809±0.0135 and 0.0626±0.0080 μg/bee, respectively. Bees exposed to lethal and sublethal doses of both insecticides experienced significant motor alterations compared to the control, except for exposure to sublethal doses of fipronil by contact. Fipronil and imidacloprid are highly toxic and promote motor changes in bees. Thus, it is important to establish management methods to reduce pollinators' exposure to these pesticides.
Keywords: Apis mellifera; Beekeeping; Behavior; Pollinators; Systemic pesticides; Toxicology